Faktor-Faktor yang Berhubungan dengan Status Gizi Balita di Desa Baumata Timur Kabupaten Kupang Tahun 2022 - Yufen Lorens Ati; Utma Aspatria; Daniela Boeky (Yayasan Pendidikan Penelitian Pengabdian Algero, 2022)
Nutritional status is a picture of the balance of nutritional intake that enters the body with what the body needs. The result of the balance of nutritional intake is optimal growth and development. Toddlers are an age group that is prone to nutritional problems, so toddlers really need optimal nutritional intake. Nutritional problems such as poor nutrition, malnutrition and nutrition occur more if the nutritional intake is unbalanced. The purpose of this study is to analyze the relationship between the number of family members, household income, household expenditure, household food security, feeding patterns, energy intake and protein intake as well as a history of infectious diseases with the nutritional status of toddlers in East Baumata Village, Kupang Regency in 2022. Types of analytical survey research or quantitative research with cross-sectional research designs. The study population, namely all mothers in Posyandu who have toddlers, totaled 256 toddlers. The sample was 72 toddlers, determined by a systematic random sampling technique. Data collection with questionnaires was then carried out chi-square tests with the help of SPSS. The results showed a significant relationship between the number of family members (0.029), household income (0.008), household expenditure (0.000), household food security (0.000), feeding patterns (0.000), energy intake (0.004) and protein intake (0.001) with the nutritional status of toddlers in East Baumata Village, Kupang Regency in 2022. Meanwhile, what is not related is a history of infectious diseases (0.091). It is recommended for mothers of toddlers to increase visits to posyandu so that toddlers get health services such as weight weighing, PB/TB measurements, immunizations and mothers obtain health information that is able to support the growth and development process of toddlers.